2010
DOI: 10.3109/08860221003615795
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E-coated cellulose acetate dialysis membrane: long-term effect on inflammation and oxidative stress

Abstract: Vitamin E supplementation by vitamin E-coated CAE dialysis membrane suppresses oxidative stress and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…Variation in plasma oxidized low density lipoprotein (Ox-LDL), nitric oxide (NOx) and thiobarbituric acid reactive substances (TBARS) were given in 11 [18,19,24,25,46,48,51,56,65,67,70] , 4 [16,22,57,62] and 8 studies [20,26,29,33,39,44,47,70] , respectively. Thirteen studies [10,20,23,26,30,33,44,48,49,51,58,64,70] reported information on total anti-oxidant status (TAS) and anti-oxidant capacity (AOC).…”
Section: Outcome Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Variation in plasma oxidized low density lipoprotein (Ox-LDL), nitric oxide (NOx) and thiobarbituric acid reactive substances (TBARS) were given in 11 [18,19,24,25,46,48,51,56,65,67,70] , 4 [16,22,57,62] and 8 studies [20,26,29,33,39,44,47,70] , respectively. Thirteen studies [10,20,23,26,30,33,44,48,49,51,58,64,70] reported information on total anti-oxidant status (TAS) and anti-oxidant capacity (AOC).…”
Section: Outcome Datamentioning
confidence: 99%
“…Five studies [32,42,51,55,69] reported information on total serum iron, 11 [17,23,27,32,34,42,51,54,55,64,69] on ferritin levels and 6 [23,32,34,42,54,55] on transferrin saturation (TSAT). Erythropoietin (EPO) dosage was specified in 16 studies [11,16,19,21,23,27,45,50,51,54,55,60,61,64,65,69] .…”
Section: Outcome Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, a small (n = 9) observational A-B study on vitamin E-coated cellulose acetate membranes compared with PF membranes [93] reported an improved and long-term control of inflammatory (high-sensitivity CRP, total antioxidant capacity, and IL-6) and oxidative stress (d-ROM test and superoxide dismutase) biomarkers.…”
Section: Vitamin E-bonded Dialyzersmentioning
confidence: 99%
“…Earlier studies have shown that both the use of vitamin E-coated membrane (VEM) dialyzers 2 and 3-hydroxy-3-methyl-glutaryl-CoA (HMGCoA)-reductase inhibitors, or statins, [3][4][5] can have anti-inflammatory and anti-oxidative effects in HD patients. [6][7][8] The primary objective of the present prospective, randomized, crossover study was to compare the effects of both treatments on sensitive markers of inflammation, oxidative stress, and endothelial cell apoptosis in patients on HD, aiming at distinguishing the different treatment effects and their time sequence on these pathogenetic routes.…”
Section: Introductionmentioning
confidence: 99%